A facile synthesis of porous bimetallic Co–Ni fluorides for high-performance asymmetric supercapacitors. Issue 20 (13th May 2020) - Zhou, Xiaoya; Qu, Xinyu; Zhao, Wen; Ren, Yanfang; Lu, Yao; Wang, Qian; Yang, Dapeng; Wang, Wenjun; Dong, Xiaochen
Abstract : Porous Co–Ni fluorides were synthesized using a two-step method and they exhibited excellent specific capacitance and cycling stability. Abstract : Exploring specific electrode active materials with excellent kinetic properties is important for the development of high performance supercapacitors. Herein, a novel nickel-cobalt fluoride (Ni1−x Cox F2 ) with a porous nanoprism structure is synthesized via step-wise recrystallization and ion-exchange reactions with a morphology control agent, namely polyvinyl pyrrolidone (PVP). The synergistic effect between the bimetallic redox centers promotes the reconstruction of the electronic coordination, leading to apparent discrepancies in the microstructure and morphology of Ni1−x Cox F2 with different stoichiometric ratios of Ni/Co. The micro-porous structure also provides sufficient interfaces and active sites for efficient electrolyte penetration and ion diffusion, thus improving its electrochemical performance. Among the as-synthesized samples, Ni0.5 Co0.5 F2, with an Ni/Co ratio of 1 : 1, achieved the highest specific capacity of 1979.6 F g −1 at 1.0 A g −1 and a remarkable long-term cycling stability of 900 F g −1 residual after 30 000 cycles at 20 A g −1 . The supercapacitor with Ni0.5 Co0.5 F2 and activated carbon as the positive and negative electrodes, respectively, delivers a high specific capacitance of 107.3 F g −1 at 1 A g −1, outstanding cycling stability of 90.07% capacity retention after 30 000 cycles, and a maximum energy density of 48.3 W h kg −1 at a power density of 952.9 W kg −1 . A flexible asymmetric all-solid-state supercapacitor based on a PVA/KOH gel electrolyte was assembled, which delivered a specific capacitance of 41.0 F g −1 at 1 A g −1 and showed promising applications in flexible electronic devices.